Cerebrotendinous Xanthomatosis: Novel EEG finding of Fixation-Off Sensitivity - Zachary Mills; James Thomas Houston; Ashley Thomas; Kelsey Shoenmeyer (Epilepsy & Behavior Reports)
Cerebrotendinous Xanthomatosis (CTX) is a rare autosomal recessive condition resulting in accumulation of cholesterol and cholestanol due to disrupted bile synthesis. Affected tissues include brain, tendons, skin, bone, lungs, and eyes. We report a clinical case presenting with epilepsy, which has been described, however with a particular EEG appearance that appears novel with Fixation-Off Sensitivity (FOS). The patient’s EEG showed significant buildup of abnormal slowing and frontally predominant generalized epileptiform discharges when her eyes were closed, and in contrast essentially normal tracings while eyes were open, eventually showing electrographic evolution and generating a bilateral tonic-clonic seizure. Genetic testing confirmed the diagnosis of CTX, and CTX-specific treatment with chonodeoxycholic acid was initiated in addition to anti-seizure medication.